ANALISIS PERHITUNGAN PENYUSUTAN AKTIVA TETAP MENURUT STANDAR AKUNTANSI KEUANGAN DAN PERATURAN PERPAJAKAN PADA CV. SAMIA SEJAHTERA - Pesak, Faneisya; Sabijono, Harijanto; Gerungai, Natalia (Universitas Sam Ratulangi, 2018)
In calculating depreciation of fixed assets may use depreciation method in accordance with financial accounting standards and tax regulations. Differences in recognition of depreciation expense will result in fiscal correction. The purpose of this study was conducted to find out how the application depreciations of methods of fixed assets according to tax regulations and financial accounting standards, as well as the impact of comparative calculations. The analytical method used is descriptive analysis method. The results show that the company has calculated depreciation expense in accordance with financial accounting standards, but there are still errors in the calculation of depreciation, and the company itself has not done the calculations in accordance with tax regulations. Any difference in depreciation expense according to financial accounting standards and tax laws will result in a positive fiscal correction resulting in the reduction of costs recognized in the commercial income statement. With the reduction of the recognition of these costs can have an impact on the addition of Income Tax (PPh). Value of PPh CV. Samia Sejahtera 2017 Rp18.323.750,00 while the value of PPh CV. Samia Sejahtera by fiscal Rp28.940.000,00 so there is a difference of Rp10.616.250,00.Keywords : Depreciation, Fixed Assets.